ORIENTASI PASAR DAN KINERJA PERUSAHAAN PADA MASA PANDEMI COVID-19: PERAN E-COMMERCE SEBAGAI MODERASI (Studi UMKM Di Kota Solo) - Sriyanto Sriyanto; Nina Adelina (Riset Manajemen dan Akuntansi, 2020)
This study aims to analyze the effect of market orientation and application of e-commerce on firm performance, and the effect of market orientation on firm performance moderated by application of e-commerce. The sample of this study is 100 entrepreneurs of SMEs in Solo city, using a purposive sampling technique. Data analysis using regression moderating analysis. The conclusion of the hypothesis test result (1) market orientation and application of e-commerce have a significant effect on firm performance. (2) application of e-commerce can moderate that reinforces the effect of market orientation on firm performance.